Patologi Birokrasi dalam Transformasi Politik Lokal: Tinjauan Terhadap Fenomena "Pajak Nanggroe" di Aceh - Ferizaldi (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
The term of Pajak Naggroe born post-conflict Vertical volume II in Aceh, with Birth of Local Government The dominant one is filled by the ex-combatant GAM (Aceh Sumatra Merdeka) The members of hearts Containers political parties Local (Partai Aceh / PA), part GAM elite are transformed Become a member local legislative besides Also An advanced as the regional administrations, entrepreneurs and others - others. But behind the phenomenon of political transformation, timbulah A new attitude among Brirokrat Aceh Nanggroe Called WITH Tax Forms Which is illegal Quotes * According to the Constitution of Indonesia but massive and commonplace * According to the new habits in Aceh. This article is trying to portray how the nanggroe tax Form hearts forming Pathology Bureaucracy in Aceh.